Clinical Outcomes Depending on Acute Blood Pressure After Cerebral Hemorrhage. Issue 1 (7th January 2019) - Toyoda, Kazunori; Koga, Masatoshi; Yamamoto, Haruko; Foster, Lydia; Palesch, Yuko Y.; Wang, Yongjun; Sakai, Nobuyuki; Hara, Takayuki; Hsu, Chung Y.; Itabashi, Ryo; Sato, Shoichiro; Fukuda‐Doi, Mayumi; et al.
Abstract : Objective: To determine the association between clinical outcomes and acute systolic blood pressure (SBP) levels achieved after intracerebral hemorrhage (ICH). Methods: Eligible patients who were randomized to the ATACH‐2 (Antihypertensive Treatment in Intracerebral Hemorrhage 2) trial (ClinicalTrials.gov : NCT01176565) were divided into 5 groups by 10‐mmHg strata of average hourly minimum SBP (<120, 120–130, 130–140, 140–150, and ≥ 150 mmHg) during 2 to 24 hours after randomization. Outcomes included: 90‐day modified Rankin Scale (mRS) 4 to 6; hematoma expansion, defined as an increase ≥6 ml from baseline to 24‐hour computed tomography; and cardiorenal adverse events within 7 days. Results: Of the 1, 000 subjects in ATACH‐2, 995 with available SBP data were included in the analyses. The proportion of mRS 4 to 6 was 37.5, 36.0, 42.8, 38.6, and 38.0%, respectively. For the "140 to 150" group relative to the "120 to 130, " the odds ratio (OR), adjusting for sex, race, age, onset‐to‐randomization time, baseline National Institutes of Health Stroke Scale score, hematoma volume, and hematoma location, was 1.62 (95% confidence interval [CI], 1.02–2.58). Hematoma expansion was identified in 16.9, 13.7, 21.4, 18.5, and 26.4%, respectively. The 140 to 150 (OR, 1.80; 95% CI, 1.05–3.09) and "≥150" (1.98; 1.12–3.51) showed a higher frequency of expansion than the 120 to 130 group. Cardiorenal events occurred in 13.6, 16.6, 11.5, 8.1, and 8.2%, respectively. The 140 to 150 (0.43; 0.19–0.88) and ≥ 150 (0.44; 0.18–0.96) showed a lower frequency of the events than the 120 to 130. Interpretation: Beneficial effects of lowering and maintaining SBP at 120 to 130 mmHg during the first 24 hours on clinical outcomes by suppressing hematoma expansion was somewhat offset by cardiorenal complications.ANN NEUROL 2019;85:105–113.